Early postoperative neurologic events are associated with worse outcome and fatal midterm survival after adult heart transplantation - Oehler, Daniel; Oehler, Hannah; Sigetti, Dennis; Immohr, Moritz Benjamin; Böttger, Charlotte; Bruno, Raphael Romano; Haschemi, Jafer; Aubin, Hug; Horn, Patrick; Westenfeld, Ralf; Bönner, Florian; Akhyari, Payam; et al. (Journal of the American Heart Association, 2023)
Background: Neurologic events during primary stay in heart transplant (HTx) recipients may be associated with reduced outcome and survival, which we aim to explore with the current study. Methods and Results We screened and included all patients undergoing HTx in our center between September 2010 and December 2022 (n=268) and checked for the occurrence of neurologic events within their index stay. Neurologic events were defined as ischemic stroke, hemorrhage, hypoxic ischemic injury, or acute symptomatic neurologic dysfunction without central nervous system injury. The cohort was then divided into recipients with (n=33) and without (n=235) neurologic events after HTx. Using a multivariable Cox regression model, the association of neurologic events after HTx and survival was assessed. Recipients with neurologic events displayed a longer intensive care unit stay (30 versus 16 days; P=0.009), longer mechanical ventilation (192 versus 48 hours; P<0.001), and higher need for blood transfusion, and need for hemodialysis after HTx was substantially higher (81% versus 55%; P=0.01). Resternotomy (36% versus 26%; P=0.05) and mechanical life support (extracorporeal life support) after HTx (46% versus 24%; P=0.02) were also significantly higher in patients with neurologic events. Covariable-adjusted multivariable Cox regression analysis revealed a significant independent association of neurologic events and increased 30-day (hazard ratio [HR], 2.5 [95% CI, 1.0-6.0]; P=0.049), 1-year (HR, 2.2 [95% CI, 1.1-4.3]; P=0.019), and overall (HR, 2.5 [95% CI, 1.5-4.2]; P<0.001) mortality after HTx and reduced Kaplan-Meier survival up to 5 years after HTx (P<0.001). Conclusions Neurologic events after HTx were strongly and independently associated with worse postoperative outcome and reduced survival up to 5 years after HTx.
Gesehen am 05.10.2023